2021
DOI: 10.3389/fvets.2021.628445
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Aspects of Ecologically Relevant Phytochemicals in Ruminant Production

Abstract: This review provides an update of ecologically relevant phytochemicals for ruminant production, focusing on their contribution to advancing nutrition. Phytochemicals embody a broad spectrum of chemical components that influence resource competence and biological advantage in determining plant species' distribution and density in different ecosystems. These natural compounds also often act as plant defensive chemicals against predatorial microbes, insects, and herbivores. They may modulate or exacerbate microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 301 publications
(385 reference statements)
0
37
1
4
Order By: Relevance
“…Although some review articles have suggested that the presence of TANs in the diet may negatively affect DMI in ruminants [1,9,57], in the present meta-analysis no changes in DMI were observed in response to dietary supplementation with TANs. This absence of changes in DMI probably occurred because the average dose of TANs used was 19.29 g kg −1 DM and negative effects of TANs on intake seem to occur with doses higher than 50 g kg −1 DM [4,9,12].…”
Section: Discussioncontrasting
confidence: 87%
“…Although some review articles have suggested that the presence of TANs in the diet may negatively affect DMI in ruminants [1,9,57], in the present meta-analysis no changes in DMI were observed in response to dietary supplementation with TANs. This absence of changes in DMI probably occurred because the average dose of TANs used was 19.29 g kg −1 DM and negative effects of TANs on intake seem to occur with doses higher than 50 g kg −1 DM [4,9,12].…”
Section: Discussioncontrasting
confidence: 87%
“…It acts agonistically on the µ-opiate and k-receptors. It acts directly onto the intestine to smoothen the muscles [57]. Thebaine acts synergistically with morphine as it helps in the synthesis of many morphine-like substances which also helps in relieving pain [27].…”
Section: Medicinal Properties Of Poppymentioning
confidence: 99%
“…Opium contains about 0.2-0.3% of the codeine which acts as an antitussive agent and helps in suppressing coughing. When ingested, it binds to the opiate receptors in the body, reducing the secretions produced by the bronchi and acts on the medulla oblongata to help in curing cough [66]. In different studies, codeine has also been demonstrated as an effective antitussive agent [67,68].…”
Section: Medicinal Properties Of Poppymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, saponins can modify rumen fermentation by suppressing protozoa and selectively inhibiting some bacteria [45]. Secondary metabolites can make the diet less susceptible to the degradation of microorganism in the rumen due to their capacity to form complexes with the components of the diet, alter the mechanisms of degradation of the microorganism or reduce their population [46]. In addition, there is a direct correlation between DMD and gas production, i.e., the higher the digestibility, the higher the gas production rate expected.…”
Section: Dry Matter Degradability In Vitro Gas Production and Phmentioning
confidence: 99%